Ripple Effects of the Trump Tariff War: Implications for South Asia in the Context of Geopolitical and Geoeconomic Dynamics - Hasan, Md Abul; Ferdos, Jannatul; Habib, Mohammad Ahsan (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
This paper explores the multifaceted effects of Donald Trump administration’s imposition of tariff policies on India through the lenses of geoeconomics and geopolitics, specifically within the South Asian context. Employing mercantilism and realism theories and utilising qualitative research methods, this paper argues and analyses that the Trump administration has adopted a transactional approach to its bilateral trade relations, notably with India. This study finds that the tariff policy toward India might have profound consequences, extending beyond bilateral trade between New Delhi and Washington, influencing the broader geopolitical and geoeconomic landscapes in the Indo-Pacific region, particularly in South Asia. Small states in South Asia may face increased complexity due to their heavy engagements with both India and the United States, especially in the absence of negotiations between the two larger economies.